2015
DOI: 10.1002/masy.201400007
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Alkyl Diazoacetates Initiated with Pd Complexes

Abstract: Summary Pd‐initiated polymerization of alkyl diazoacetates as an effective methodology to prepare carbon‐carbon (CC) main chain polymers bearing a substituent on every main chain carbon is described. (NHC)Pd/borate (NHC = N‐heterocyclic carbene) systems are efficient at affording high Mn polymers. π‐AllylPdCl‐based systems can initiate the polymerization with the number of polymer chain per Pd ratios over 1.0 because of occurrence of chain transfer, capable of affording relatively low Mn polymers in high yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The resonance of the mainchain carbon of poly-1 50 was split into two peaks located at 45.0 and 46.5 ppm, consistent with the 1 H NMR analysis. 16 Note that the main-chain carbon of a fully atactic polycarbene usually showed multiple resonances from 43 to 48 ppm in 13 C NMR, suggesting the poly-1 50 obtained may possess some content of stereoregularity. 16,17 The 13 C resonances of the carbonyl carbon of poly-1 50 showed a major signal at 170.0 ppm accompanied by a minor signal at 171.1 ppm.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The resonance of the mainchain carbon of poly-1 50 was split into two peaks located at 45.0 and 46.5 ppm, consistent with the 1 H NMR analysis. 16 Note that the main-chain carbon of a fully atactic polycarbene usually showed multiple resonances from 43 to 48 ppm in 13 C NMR, suggesting the poly-1 50 obtained may possess some content of stereoregularity. 16,17 The 13 C resonances of the carbonyl carbon of poly-1 50 showed a major signal at 170.0 ppm accompanied by a minor signal at 171.1 ppm.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…16 Note that the main-chain carbon of a fully atactic polycarbene usually showed multiple resonances from 43 to 48 ppm in 13 C NMR, suggesting the poly-1 50 obtained may possess some content of stereoregularity. 16,17 The 13 C resonances of the carbonyl carbon of poly-1 50 showed a major signal at 170.0 ppm accompanied by a minor signal at 171.1 ppm. On the basis of the pioneering works of Ihara and de Bruin, the resonance at 171.1 ppm can be ascribed to syndiotactic polycarbene.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pioneering work by the groups of Ihara and de Bruin demonstrated that polymerization of ethyl diazoacetate (EDA) and other α-diazocarbonyl compounds, functional carbene precursors, could be initiated by homogeneous palladium , and rhodium species (Figure B): the former generally yield atactic polymers, and the latter, syndiotactic ones. , Yet, controlled and living polymerization of α-diazocarbonyl compounds has been a crucial challenge: in one case control could be attained by alcohol/water-mediated chain transfer, and only two reported systems exhibited control and livingness, of which one , did not generalize beyond cyclotriphosphazene-containing monomers. Furthermore, formation of maleate and fumarate esters and analogous carbene dimers plagues most existing methods and compromises the polymer yield (Figure B). ,,, Although theoretical and mechanistic studies have been carried out for some initiators, particularly based on Rh, ,, numerous aspects of initiation and propagation remain ill-defined, which has inhibited progress.…”
mentioning
confidence: 99%
“…Furthermore, for-mation of maleate and fumarate esters and analogous carbene dimers plagues most 15 existing methods and compromises the polymer yield (Figure 1B). 5,7,11,15 Although theoretical and mechanistic studies have been carried out for some initiators, particularly based on Rh, 15,18,24 numerous aspects of initiation and propagation remain ill-defined, which has inhibited progress.…”
mentioning
confidence: 99%